Aspects of protein and amino acid metabolism in a model of severe glutamine deficiency in sepsis - Safránek, Roman; Holecek, Milan; Sispera, Ludek; Muthný, Tomás (Annals of nutrition & metabolism, 2006)
BACKGROUND/AIMS: Growth hormone (GH) could have the potential to improve protein metabolism in sepsis but glutamine deficiency has been reported after GH treatment. The aim was to investigate the effects of glutamine deficiency in sepsis with and without GH treatment on protein and amino acid metabolism. METHODS: Cecal ligation and puncture (CLP) was used as a model of sepsis. Serious glutamine deficiency was induced by administration of glutamine synthetase inhibitor, methionine sulfoximine (MSO). Young Wistar rats were divided into 5 groups: control; CLP; CLP+MSO; CLP+GH, and CLP+MSO+GH. Parameters of protein metabolism were measured on incubated soleus and extensor digitorum longus muscles: [1-14C]leucine was used to estimate protein synthesis and leucine oxidation, tyrosine release was used to evaluate protein breakdown. Amino acid concentrations in plasma, skeletal muscle and incubation media were measured by HPLC. RESULTS/CONCLUSIONS: A reduced muscle glutamine concentration after MSO treatment is not associated with changes in the rates of protein synthesis or breakdown. MSO treatment decreased glutamine release from skeletal muscle and plasma glutamine concentration. Severe glutamine deficiency in GH-treated septic rats resulted in increased release of branched-chain amino acids from skeletal muscle.
Keywords: Random Allocation; Growth Hormone; Rats; Sepsis; svalové proteiny; Rats, Wistar; Chromatography, High Pressure Liquid; Muscle, Skeletal; Glutamine; vysokoúčinná kapalinová chromatografie; krysa rodu Rattus; ženské pohlaví; zvířata; kosterní svaly; náhodné rozdělení; sepse; Muscle Proteins; glutamin; růstový hormon; potkani Wistar; Female; aminokyseliny; Amino Acids; Animals